Next-Generation Heterocyclic Electrophiles as Small-Molecule Covalent MurA Inhibitors - Péter Ábrányi-Balogh; Aaron Keeley; György G. Ferenczy; László Petri; Tímea Imre; Katarina Grabrijan; Martina Hrast; Damijan Knez; Janez Ilaš; Stanislav Gobec; György M. Keserű (MDPI AG, 2022)
Heterocyclic electrophiles as small covalent fragments showed promising inhibitory activity on the antibacterial target MurA (UDP-N-acetylglucosamine 1-carboxyvinyltransferase, EC:2.5.1.7). Here, we report the second generation of heterocyclic electrophiles: the quaternized analogue of the heterocyclic covalent fragment library with improved reactivity and MurA inhibitory potency. Quantum chemical reaction barrier calculations, GSH (L-glutathione) reactivity assay, and thrombin counter screen were also used to demonstrate and explain the improved reactivity and selectivity of the N-methylated heterocycles and to compare the two generations of heterocyclic electrophiles.